The haunted heart and the Holy Ghost: on retrieval, donation and death - Hordern, J (BMJ Publishing Group, 2020)
This enquiry examines problems which haunt the “heart” and its donation. It begins by examining the heart’s enduring significance for culturally mediated self-understanding, vulnerability to misunderstanding and abuse and relevance to challenging the determination of death by neurological criteria. Despite turns to brain-centred selfconceptions, the heart remains haunted by the hybrid experiences of identity accompanying organ transplant, the relational significance attached to dead hearts witnessed in the Alder Hey scandal and claims that heart transplants commonly constitute the legitimate killing of a person. To explore these phenomena, traditions are retrieved in which the heart-as-organ was construed in terms of a person’s core identity. Influential Abrahamic beliefs about ‘the heart’ are considered in order to explore explanations for why the heart remains culturally preeminent, to make intelligible our haunted hearts and to examine possible violations of solidarity in organ donation practice. Jewish and Christian Scriptures are exegeted to illumine the sources of our haunting and address the desire for holistic bodily life. In these sources, the heart is the seat of affections, intelligence and agency but requires healing, conceived via the surgical metaphors of heart transplant and circumcision, if people are to join the insightful, solidary path of pilgrimage. Absent healing, the heart experiences a judgment of the whole person – organ-andcore – at the moment of death. Through such exegesis, the doctrine of the Holy Ghost emerges as a way to make intelligible, though not dispel, the heart’s haunting. The doctrine’s practical significance concerns the possibility of social unity among hearts, “intercordiality”, which construes people within a covenantal life of pilgrimage which encourages heart donation in certain circumstances, makes intelligible the Alder Hey parents’ experience of social misunderstanding and rejects ascribing any legitimacy in medical culture to the consensual killing of patients for the sake of retrieving their organs.